Choline transport in Saccharomyces cerevisiae. - Hosaka, K (1980)
Choline transport of Saccharomyces cerevisiae was measured by the filtration method with the use of glass microfiber paper. The uptake was time and temperature dependent. The kinetics of choline transport showed Michaelis behavior; an appearent Km for choline was 0.56 microM. N-Methylethanolamine, N,N-dimethylethanolamine, and beta-methylcholine were competitive inhibitors of choline transport, with Ki values of 40.1, 3.1, and 6.9 microM, respectively. Ethanolamine, phosphorylcholine, and various amino acids examined had no effect. Choline transport required metabolic energy; removal of glucose resulted in a great loss of transport activity, and the remaining activity was abolished by 2,4-dinitrophenol, carbonyl cyanide p-trifluoromethoxyphenyl hydrazone, arsenate, and cyanide. External Na+ was not required, and the transport was not effected by ionophores, valinomycin, and gramicidin D. These results indicate that S. cerevisiae possess an active choline transport system mediated by a specific carrier. This view is further supported by the isolation and characterization of a choline transport mutant. The choline transport activity in this mutant was very low, whereas the transport of L-leucine, L-methionine, D-glucose, and myo-inositol was normal. Together with the choline transport mutant, mutants defective in choline kinase were also isolated.